How do Primary School Teachers Create Meaningful Learning Environment to Motivate Students? - Ustilaitė, Stasė; Poteliūnienė, Sniegina; Juškevičienė, Agnė; Sabaliauskas, Stanislav (Pedagogika, 2023)
The qualitative research aimed to reveal how a teacher creates a meaningful learning environment for primary school students in order to stimulate their motivation for learning. Eight primary school teachers participated in the focus group interviews. During the inductive analysis of the research data, five thematic categories were identified, that reflected the types of teachers activities encouraging students to learn and creating preconditions for meaningful learning of students.